Hydrogen bonding and covalent coupling in adsorbed molecular monolayers - Garfitt, Jason Michael (2014)
This thesis examines multiple different molecular networks adsorbed on several different substrates, namely, highly oriented pyrolytic graphite (HOPG), Au(111) and graphene. STM investigations into hydrogen-bonded structures formed by closely related tetracarboxylic acid molecules were performed. The molecule pterphenyl-3,5,3,5-tetracarboxylic acid (TPTC), which is known to form random tiling networks, was observed on a graphene on copper substrate. The network formed from deposition of TPTC from nonanoic acid was examined statistically. Aqueous solutions of TPTC were also examined on HOPG where a new structure, distinct from the random tiling, was observed. Aqueous solutions of related molecules biphenyl-3,3',5,5'-tetracarboxylic acid (BPTC) and quaterphenyl-3,3',5,5'-tetracarboxylic acid (QPTC), were also studied on HOPG. QPTC formed a similar structure to the aqueous solutions of TPTC, but BPTC formed two different phases, one of which was a kagome network.